1992
DOI: 10.1113/jphysiol.1992.sp019357
|View full text |Cite
|
Sign up to set email alerts
|

The effect of succinylcholine on cat gastrocnemius muscle spindle afferents of different types.

Abstract: SUMMARY1. A population of 269 gastrocnemius muscle spindle afferents have been studied in anaesthetized cats for the effects of succinylcholine (SCh) on their response to ramp and hold stretches repeated every 6 s. The effectiveness and reliability of the SCh test was improved by prior stimulation of the muscle at 10 Hz for 30 s to increase the blood flow.2. Responses have been assessed from averaged cycle histograms before and after a single iv. dose of SCh of 200 jag kg-'. As for previous studies of jaw musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 15 publications
2
43
1
Order By: Relevance
“…We classified units whose dynamic response was greatly increased by suxamethonium as spindle primary afferents. This is a reasonably secure criterion (Taylor, Rodgers, Fowle & Durbaba, 1992). However, Taylor et al (1992) have shown that about half of the gastrocnemius spindles whose resting discharge is increased by suxamethonium, but whose dynamic response is not appreciably affected (i.e.…”
Section: Chronic Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…We classified units whose dynamic response was greatly increased by suxamethonium as spindle primary afferents. This is a reasonably secure criterion (Taylor, Rodgers, Fowle & Durbaba, 1992). However, Taylor et al (1992) have shown that about half of the gastrocnemius spindles whose resting discharge is increased by suxamethonium, but whose dynamic response is not appreciably affected (i.e.…”
Section: Chronic Recordingsmentioning
confidence: 99%
“…This is a reasonably secure criterion (Taylor, Rodgers, Fowle & Durbaba, 1992). However, Taylor et al (1992) have shown that about half of the gastrocnemius spindles whose resting discharge is increased by suxamethonium, but whose dynamic response is not appreciably affected (i.e. units we would classify as spindle secondaries), have conduction velocities in the spindle primary afferent range.…”
Section: Chronic Recordingsmentioning
confidence: 99%
“…3D). Measures of increments in initial frequency and dynamic difference (peak frequency minus initial frequency) after SCh were taken as indices of effects exerted through static and dynamic primary spindle afferents, respectively (for a detailed description, see Taylor et al, 1992;Durbaba et al, 2006). In so doing, six neurons were considered to be affected by static bag2 primary spindle afferents, four cells by static/dynamic (bag1/ bag2) primaries, and two neurons by dynamic bag1 primary spindle afferents.…”
Section: Characterization Of Proprioceptive Neuronsmentioning
confidence: 99%
“…In primary afferents this procedure seems to enhance the rapid adaptation phase, which is thought to be due to a property of the ending rather than of the intrafusal muscle fibres. This matter is considered further in the following paper (Taylor, Rodgers, Fowle & Durbaba, 1992).…”
mentioning
confidence: 99%